PSI-18 Rumen fluid metabolites associated with feed efficiency in Angus steers. (5th December 2019) - Clemmons, Brooke A; Henniger, Madison T; Powers, Joshua B; Embree, Mallory M; Voy, Brynn H; Myer, Phillip R
Abstract: The functional capacity of the rumen is central to ruminant feed efficiency, and therefore, differences in ruminal metabolism may contribute to cattle feed efficiency variations. The objective of this study was to determine differences in rumen metabolites associated withvariations in feed efficiency. Fifty steers were utilized and maintained on a backgrounding diet (11.57% CP; 76.93% TDN DM basis; 28 mg monensin/kg DM) for 70 days following a two-week diet adaptation. Feed intake was monitored using the GrowSafe system. Following the 70-day trial, steers were ranked by residual feed intake (RFI) and divided into low- (n = 14) and high-RFI (n = 15) based on RFI ±0.5 SD around the mean. On day 70, rumen fluid was collected viaorogastric tubing and filtered through a 0.22 μM syringe filter. Untargeted metabolomics wasconducted utilizing the Dionex UltiMate 3000 UPLC system and electrospray ionization used tointroduce samples into an Exactive Plus Orbitrap MS. Eighty-eight known metabolites wereidentified using MAVEN. Metabolites were median-centered, log-transformed, and pareto-scaled using Metaboanalyst 4.0. Normality was assessed using the SAS 9.4 PROC UNIVARIATE procedure. Normal distribution was considered based on a Shapiro-Wilk score of ≥ 0.85 andvisual analysis of histogram and plots of residuals. Normally distributed metabolites wereanalyzed using one-way ANOVA in SAS with Tukey's HSD post-hoc test, whereas non-normally distributed variables were analyzed using Wilcoxon Rank Sum and Kruskal Wallis H test. Significance was set at P ≤ 0.05. Eight metabolites differed between high- and low-RFI steers. Twelve metabolites identified as having > two-fold change between low- and high-RFI steers, including 3, 4-Dihydroxyphenylacetate and sulfolactate. Orthogonal PLSDA revealed overlap ofrumen fluid metabolites from high- and low-RFI steers. Understanding rumen metabolites in high- and low-RFI steers will provide researchers with information to identify more efficient cattle.